Rozwój złożonych organizmów gospodarczych - Sobotkiewicz, Dariusz (Development of Complex Enterprises, 2008)
The article tries to present complex enterprises' development. The main focus is on geographical expansion as a development's ground of big economic entities. There are also presented various types of organizational structures of multiadministrative subjects for which territorial expansion determines various location of organizational entities for marketing in the structure of enterprises' types.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 324-331